Legal Protection for Patients in Online Health Service Agreements: A Normative Analysis of Structural Gaps and Reform Imperatives in Indonesia’s Telemedicine Regulatory Framework - Sari, Patma; Rosnida; Irabiah; Beni Suswanto; Yeni haerani (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Purpose: This study aims to evaluate the adequacy of Indonesia’s regulatory framework in protecting patients within online health service agreements and to identify structural normative gaps that require legislative reform. Methods: Employing a normative legal research methodology combining statutory and conceptual approaches, the study analyzes primary legal sources including Law No. 17 of 2023 on Health, Government Regulation No. 28 of 2024, and Minister of Health Regulation No. 20 of 2019 on Inter-Facility Telemedicine Services (which primarily governs telemedicine between health facilities rather than direct doctor-patient teleconsultation through third-party applications), alongside consumer protection legislation and civil law principles, as well as secondary sources including academic literature and judicial decisions. Results: The findings reveal that the existing regulatory framework remains fragmented and contains structural gaps that undermine substantive legal protection for patients, particularly in determining professional liability when medical errors occur through digital platforms, ensuring the validity of electronic informed consent, and providing accessible remedies for aggrieved patients. The regulatory oversight body for personal data protection is still being strengthened, further limiting enforcement effectiveness. Conclusions: Indonesia urgently requires a comprehensive and integrated telemedicine statute that explicitly addresses the unique contractual and liability dimensions of digital health services, establishes clear data governance standards, defines platform operator responsibilities, and creates a dedicated dispute resolution mechanism suited to the online health environment. This study contributes to the field by offering a systematic normative mapping of existing gaps and proposing a concrete legislative reform agenda distinct from prior scholarship that addressed only general physician-patient relationships.